Functional anatomy of autobiographical memory recall deficits in depression - Young, K. D. (Cambridge University Press, 2012)
BACKGROUND: Major depressive disorder (MDD) is associated with deficits in recalling specific autobiographical memories (AMs). Extensive research has examined the functional anatomical correlates of AM in healthy humans, but no studies have examined the neurophysiological underpinnings of AM deficits in MDD. The goal of the present study was to examine the differences in the hemodynamic response between patients with MDD and controls while they engage in AM recall. METHOD: Participants (12 unmedicated MDD patients; 14 controls) underwent functional magnetic resonance imaging (fMRI) scanning while recalling AMs in response to positive, negative and neutral cue words. The hemodynamic response during memory recall versus performing subtraction problems was compared between MDD patients and controls. Additionally, a parametric linear analysis examined which regions correlated with increasing arousal ratings. RESULTS: Behavioral results showed that relative to controls, the patients with MDD had fewer specific (p=0.013), positive (p=0.030), highly arousing (p=0.036) and recent (p=0.020) AMs, and more categorical (p<0.001) AMs. The blood oxygen level-dependent (BOLD) response in the parahippocampus and hippocampus was higher for memory recall versus subtraction in controls and lower in those with MDD. Activity in the anterior insula was lower for specific AM recall versus subtraction, with the magnitude of the decrement greater in MDD patients. Activity in the anterior cingulate cortex was positively correlated with arousal ratings in controls but not in patients with MDD. CONCLUSIONS: We replicated previous findings of fewer specific and more categorical AMs in patients with MDD versus controls. We found differential activity in medial temporal and prefrontal lobe structures involved in AM retrieval between MDD patients and controls as they engaged in AM recall. These neurophysiological deficits may underlie AM recall impairments seen in MDD.